In Vitro Evaluation of the Antioxidant, 3,5-Dihydroxy-4-ethyl-trans-stilbene (DETS) Isolated from Bacillus cereus as a Potent Candidate against Malignant Melanoma - Nath, Lekshmi R.; Kumar, S. N.; Das, Arya A.; Nambisan, Bala; Shabna, A.; Mohandas, Chellapan; Anto, Ruby John (Frontiers in Microbiology, 2016)
3,5-dihydroxy-4-ethyl-trans-stilbene (DETS) is a natural stilbene, which was first identified as bioactive bacterial secondary metabolite isolated from Bacillus cereus associated with a rhabditid entomopathogenic nematode. The present study was intended to investigate the antioxidant and anticancer activity of this compound in vitro. Antioxidant activity was investigated by assaying DPPH free radical scavenging, superoxide radical-(O2−) scavenging, hydroxyl radical scavenging and metal chelating activity, which proved that the compound is a powerful antioxidant. The metal chelating activity of DETS was higher than butylated hydroxyanisol (BHA) and gallic acid, two well-known antioxidants. As the molecule exhibited strong antioxidant potential, it was further evaluated for cytotoxic activity towards five cancer cells of various origins. Since the compound has a strong structural similarity with resveratrol (trans-3,4,5-trihydroxystilbene), a well-studied chemopreventive polyphenolic antioxidant, its anticancer activity was compared with that of resveratrol. Among the five cancer cells studied, the compound showed maximum cytotoxicity towards the human melanoma cell line, A375 (IC50: 24.01 μM) followed by cervical [HeLa- 46.17 μM], colon [SW480- 47.28 μM], liver [HepG2- 69.56 μM] and breast [MCF-7- 84.31 μM] cancer cells. A375 was much more sensitive to DETS compared to the non-melanoma cell line, A431, in which the IC50 of the compound was more than double (49.60 μM). In the present study, the anticancer activity of DETS against melanoma was confirmed by various apoptosis assays. We also observed that DETS, like resveratrol, down-regulates the expression status of major molecules contributing to melanoma progression, such as BRAF, β-catenin and Brn-2, all of which converge in MITF-M, the master regulator of melanoma signaling. The regulatory role of MITF-M DETS-induced cytotoxicity in melanoma cells was confirmed by comparing the cytotoxicity of DETS in A375 cells (IC50-24.1 μM), with that in SK-MEL-2 (IC50-67.6 μM), another melanoma cells which highly over-express MITF-M. The compound arrests the cells at S- G2 transition state of the cell cycle, as resveratrol. Our results indicate that DETS is a powerful antioxidant, having anticancer efficacy comparable with that of resveratrol, and is a potential candidate to be explored by in vivo studies and in-depth mechanistic evaluation. To our knowledge, this is the first report